A series of cutaneous manifestations in a patient with vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic syndrome - Anne-Sophie Groleau; Alex Derstenfeld; Steffany Poupart; Isabelle Marcil (SAGE Open Medical Case Reports)
Vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic is a rare, autoinflammatory disorder caused by a somatic mutation of ubiquitin-activating enzyme 1. Common systemic manifestations include fever, neutrophilic dermatoses, relapsing polychondritis, and pulmonary manifestations. Cutaneous manifestations are frequently the initial presentation and are a marker of systemic disease. Here, we present an unusual case of a 71-year-old man with multiple cutaneous manifestations of vacuoles, E1 enzyme, X-linked, autoinflammatory, and somatic syndrome occurring simultaneously.